ЕЛЕКТРИЧНЕ ПОЛЕ НАПІВПРОВІДНОГО ЕКРАНА СИЛОВОГО КАБЕЛЮ З ПОЛІМЕРНОЮ ІЗОЛЯЦІЄЮ З УРАХУВАННЯМ СТРУКТУРНИХ НЕОДНОРІДНОСТЕЙ - Щерба, А.А.; Подольцев, О.Д.; Кучерява, І.М. (Інститут електродинаміки НАН України, Київ, 2024)
The non-homogeneous electric field distributions in the cross-linked polyethylene insulation of 330 kV power cable with multi-conductor core depending on the electrical conductivity and thickness of the semiconducting screen as well as at different frequency of applied voltage (from 50 to 104 Hz) are studied by finite-element analysis. As shown, taking into account the periodic structure of core surface, the electrical conductivity of the material of internal semiconducting screen should exceed 10–6 S/m and its thickness should be at least 1.5 mm in order to obtain the uniform electric field in the basic insulation of the cable at the boundary with the screen. The paper also considers the effect of various types of the surface and volumetric defects in the semiconducting screen on the electric field inhomogeneity in cable insulation. It is shown that the defects in the screen can lead to a significant increase of the electric field in the local zones of their location (up to 5 times as compared to the field without defects) and therefore contribute to the formation and development of treeing structures in the insulation. The revealed results explain the reasons for the micro- and macro-level degradation of power cable insulation and confirm the need to ensure the uniform structure, smooth surface of both semiconducting screen and core during the technological process of manufacturing the power cables with cross-linked polyethylene insulation. References 23, figures 8, table 1.